Hardness and Non-Approximability of Bregman Clustering Problems. - Ackermann, Marcel R; Blömer, Johannes; Scholz, Christoph

How to Share a Secret - Blömer, Johannes (Algorithms Unplugged)

Income Determination and Income Discrimination in Shenzhen - Gries, Thomas; Gravemeyer, Stefan; Xue, Jinjun (Urban Studies)

Financial Deepening, Trade Openness and Economic Growth in Latin America and the Caribbean - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (Applied Economics)

Causal Linkages Between Domestic Terrorism and Economic Growth - Gries, Thomas; Krieger, Tim; Meierrieks, Daniel (Defence and Peace Economics)

Interregional Migration, Self-selection and the Returns to Education in Brazil - Gries, Thomas; Kraft, Manfred; Piek, Christina (The Annals of Regional Science)

Short Signatures from Weaker Assumptions - Hofheinz, Dennis; Jager, Tibor; Kiltz, Eike (Advances in Cryptology - ASIACRYPT 2011 - 17th International Conference on the Theory and Application of Cryptology and Information Security, Seoul, South Korea, December 4-8, 2011. Proceedings)

How to break XML encryption - Jager, Tibor; Somorovsky, Juraj (Proceedings of the 18th ACM Conference on Computer and Communications Security, CCS 2011, Chicago, Illinois, USA, October 17-21, 2011)

Bounded Retransmission in Event-B{\(\parallel\)}CSP: a Case Study - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Mechanically verified proof obligations for linearizability - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (ACM Trans. Program. Lang. Syst.)

ReL: A Generic Refactoring Language for Specification and Execution - Ruhroth, Thomas; Wehrheim, Heike; Ziegert, Steffen (37th EUROMICRO Conference on Software Engineering and Advanced Applications, SEAA 2011, Oulu, Finland, August 30 - September 2, 2011)

Verifying Linearisability with Potential Linearisation Points - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (FM 2011: Formal Methods - 17th International Symposium on Formal Methods, Limerick, Ireland, June 20-24, 2011. Proceedings)

Sound and Complete Abstract Graph Transformation - Steenken, Dominik; Wehrheim, Heike; Wonisch, Daniel (Formal Methods, Foundations and Applications - 14th Brazilian Symposium, SBMF 2011, São Paulo, Brazil, September 26-30, 2011, Revised Selected Papers)

A CSP Account of Event-B Refinement - Schneider, Steve; Treharne, Helen; Wehrheim, Heike (Proceedings 15th International Refinement Workshop, Refine@FM 2011, Limerick, Ireland, 20th June 2011.)

Zuverlässigkeitsorientierte Mehrzieloptimierung zur Aktorrekonfiguration eines X-by-wire-Fahrzeugs - Sondermann-Wölke, Christoph; Sextro, Walter; Reinold, Peter; Trächtler, Ansgar (Technische Zuverlässigkeit TTZ)

Eine Reduktionsmethode zur Ableitung elektromechanischer Ersatzmodelle für piezoelektrische Wandler unter Verwendung der Finite-Elemente- Methode (FEM) - Krol, Rafal

Associations between the macronutrient composition of the evening meal and average daily sleep duration in early childhood - Diethelm, Katharina; Remer, Thomas; Jilani, Hannah; Kunz, Clemens; Buyken, Anette (Clinical Nutrition)

Dietary glycaemic index and glycaemic load among Australian children and adolescents - Chun Yu Louie, Jimmy; Buyken, Anette; Heyer, Kristina; Flood, Victoria M. (British Journal of Nutrition)
There are no published data regarding the overall dietary glycaemic index (GI) and glycaemic load (GL) of Australian children and adolescents. We therefore aim to describe the dietary GI and GL of participants of the 2007 Australian National Children's Nutrition and Physical Activity Survey (2007ANCNPAS), and to identify the main foods contributing to their GL. Children, aged 2–16 years, who provided two 24 h recalls in the 2007ANCNPAS were included. A final dataset of 4184 participants was analysed. GI of each food item was assigned using a previously published method. GL was calculated, and food groups contributing to the GL were described by age group and sex. The weighted mean dietary GI and GL of the participants were 54 ( sd 5) and 136 ( sd 44), respectively. Among the nutrients examined, Ca had the highest inverse relationship with GI ( P < 0·001), while percentage energy from starch was most positively associated with GI. The association between fibre density and GI was modest, and percentage energy from sugar had an inverse relationship with GI. Daily dietary GL contributed by energy-dense and/or nutrient-poor (EDNP) items in subjects aged 14–16 years was more than doubled that of subjects aged 2–3 years. To conclude, Australian children and adolescents were having a high-GI dietary pattern characterised by high-starchy food intake and low Ca intake. A significant proportion of their dietary GL was from EDNP foods. Efforts to reduce dietary GI and GL in children and adolescents should focus on energy-dense starchy foods.

Consumption of dietary salt measured by urinary sodium excretion and its association with body weight status in healthy children and adolescents - Libuda, Lars; Kersting, Mathilde; Alexy, Ute (Public Health Nutrition)
Abstract Objective Highly processed foods such as convenience foods usually have a high salt content and therefore might indirectly act as adipogenic due to an increasing consumption of sugar-containing beverages (SCB). We examined the association between dietary salt and body weight status. Design We used data on urinary Na excretion as an indicator of dietary salt and BMI standard deviation score (BMI-SDS) and percentage body fat (%BF) of children and adolescents participating in the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study. Setting Dortmund, Germany. Subjects Children and adolescents ( n 364) who had at least two 24 h urine samples and two dietary records in the observational period between 2003 and 2009 were considered in our data analysis. Results Repeated-measures regression models revealed that urinary Na was positively associated with BMI-SDS (+0·202 SDS/g Na excretion at baseline; P < 0·001) and %BF (+1·303 %BF/g Na excretion at baseline; P < 0·01) at baseline in boys and girls. These associations remained significant after adjustment for SCB consumption and total energy intake. Furthermore, there was a positive trend between baseline Na excretion and the individual change in %BF in the study period (+0·364 increase in %BF/g Na excretion at baseline), which was confirmed after inclusion of SCB consumption or total energy intake. There was no significant association between the change in Na excretion and the concurrent change of either BMI-SDS or %BF in any model. Conclusions Our results suggest that a high intake of processed salty foods could have a negative impact on body weight status in children and adolescents independently from their consumption of SCB.

24h-Sodium excretion and hydration status in children and adolescents - Results of the DONALD Study - Alexy, Ute; Cheng, Guo; Libuda, Lars; Hilbig, Annett; Kersting, Mathilde (Clinical Nutrition)